TRENDS OF SELF MEDICATION IN PATIENTS WITH ACNE VULGARIS - Tanzeela Khalid; Tariq Iqbal (Journal of University Medical & Dental College)
ABSTRACT Back ground: Self medication is a norm in our country. One factor probably contributing to this phenomenon is over the counter sale of almost all medication without any regulation. In our dermatology practice, we frequently encounter patients with acne vulgaris deteriorated by topical use of self medication. However, there is very little data to support this in our set up. Objective: To determine the percentage of acne patients using self medication in our population. Design: A cross-sectional survey. Patients and methods: One hundred and fifty patients, of any age and either sex, presenting at outpatient dermatology clinics (Madina Teaching Hospital and Faisal Hospital, Faisalabad), from June to September 2009, for the treatment of acne vulgaris were included. An in-person interview using a questionnaire was conducted. They were asked about the use of self medication for their disease. Details of type of medication, its effects on disease and the source of advice were also noted. Objective assessment of acne grade was done by trained dermatology personnel. Data was analyzed using micro software SPSS version 17. Results: Show that 115(77%) patients had used self medication. Potent topical steroids were used by 72(48%) patients. Majority of the patients received the advice about self medication from their friends (31%) or relatives (27%). Temporary improvement was noticed by 47% of those who used self medication. Conclusion: A significantly high percentage of patients (77%) in our population use self medication for acne vulgaris.